La educación mediática como política educativa: el caso peruano - Mateus, Julio-César (2020)
Unlike other countries, Peru does not have a tradition of critical media education. On the contrary, the paradigm that has prevailed in the Peruvian educational policy in the last 30 years has been to provide technology to schools, obtaining very limited results. The public policy of recent years has been linked to the purchase of hardware and software rather than thinking the media as an object of study that must be incorporated in schools. This paradigm of provision of technologies fails in two debatable premises: first, that ICTs are an end in itself and that their integration is intended to facilitate the teaching process; and second, that their integration into the school responds to an economic criterion of development of working capital, rather than to a political right to develop citizenship. In this paper, we address the situation of initial teacher training in Peru, based on an instrument that measures the perception of future teachers about media education.